Incidence, temporal trends and potential risk factors for prosthetic joint infection after primary total shoulder and elbow replacement: Systematic review and meta-analysis. Issue 4 (April 2020) - Kunutsor, Setor K.; Barrett, Matthew C.; Whitehouse, Michael R.; Craig, Richard S.; Lenguerrand, Erik; Beswick, Andrew D.; Blom, Ashley W.
Highlights: PJI incidence following total shoulder replacement is 0.61% over 1-year follow-up. PJI incidence following total elbow replacement is 2.53% over 3 years follow-up. There may be a temporal decline in shoulder and elbow PJI incidence. Shoulder PJI is increased in young males, previous shoulder surgery and sleep apnoea. High BMI, psychiatric illness and previous elbow surgery increase elbow PJI risk. Summary: Objectives: We conducted a systematic meta-analysis to evaluate the incidence, temporal trends and potential risk factors for prosthetic joint infection (PJI) following primary total shoulder replacement (TSR) and elbow replacement (TER). Methods: Longitudinal studies reporting infection outcomes following primary TSR or TER were sought from MEDLINE, Embase and Cochrane Library up to June 2019. Incidence rates and relative risks (with 95% CIs) were calculated. Results: The search identified 105 eligible articles (108 non-overlapping studies). There were 631, 854 TSRs (1, 751 PJIs) and 17, 485 TERs (525 PJIs). The pooled PJI incidence following TSR was 0.61% (0.34–0.93) over a follow-up period of 1.1 years. The corresponding incidence following TER was 2.53% (1.99–3.12) over a follow-up period of 3.3 years. Shoulder and elbow PJI incidence declined from the 1990s to 2010 and beyond. Males, younger age (<75 years), previous shoulder surgery, reverse TSR, rotator cuff arthropathy and inpatient TSR increased shoulder PJI risk. For TER, high body mass index, psychiatric illness, and previous elbow surgery increased PJI risk. Conclusions: Shoulder and elbow PJI may be on a temporal decline. Caution should be taken for patients at high PJI risk following primary TSR such as younger males and patients with a previous shoulder surgery.